The PIBID and its Contribution in Teacher Education in Geography: Experience of the scholars of the State University of Alagoas-UNEAL / O PIBID e sua Contribuição na Formação Docente em Geografia: Experiência das Bolsistas da Universidades Estadual de AlagoasUNEAL - Sirlange Soares da Silva Brito; Cristiane da Silva; Elayne Cristina Pereira dos Santos (Universidade Estadual de Alagoas, 2019)
The present work intends to discuss the importance of the Institutional Program of Initiation Scholarship to Teaching - PIBID in the training of teachers in geography. The PIBID is an important teacher training policy, for it extends the training link, as well as close ties between universities and schools of the Public Education Network, offering new opportunities for undergraduate students in geography in innovative learning methods, contributing positively in educational activities, breaking the rigidity of mechanical knowledge. The main objective of the experience report was to present the activities carried out by PIBID scholarship students, who worked in State Schools located in the City of União dos Palmares-AL, in partnership with the State University of Alagoas-UNEAL. We sought to analyze the benefits to the graduates in geography included in the program. It should be noted that during academic training a range of geographical knowledge is acquired, and that through programs such as PIBID, scholarship students have the opportunity to expose in practice all their knowledge. The program also has the incentive to encourage the improvement of teaching-learning institutions and in the training of professionals capable of instigating the discussion about the reality of the city, the neighborhood, the street, the State, the region and the country in the classroom, besides pedagogical valorization, developments and applications of new methodologies in the teaching / learning process.